Plato's Epistemology Being and Seeming - Moss, Jessica (Oxford University Press, Incorporated, 2021)
Plato's Epistemology presents an original interpretation of one of the central topics in Plato's work: epistemology. Moss argues, against the grain of much modern scholarship, that Plato's epistemology is radically different from our own
Keywords: Plato -- v427-v347; Plato; Knowledge, Theory of; Erkenntnistheorie; Electronic books